Perceptions of Elder Abuse From Community-Dwelling Older Persons and Professionals Working in Western Switzerland - Roulet Schwab, Delphine (Journal of interpersonal violence, 2021)
Older persons’ perspectives regarding elder abuse remain little studied. However, definitions of elder abuse and effective prevention strategies require adaptation to the needs and cultures of targeted populations. This study explored the views of older persons and professionals to evaluate their converging and diverging perspectives toward elder abuse and its prevention. The study employed a qualitative approach where six focus groups were held in Western Switzerland (the French-speaking part of the country). Four focus groups with 25 older persons from varying socioeconomic backgrounds, and the other two focus groups were carried out with 16 professionals working in the field of elder abuse prevention. For the focus groups, we used the technique of free associations to begin the discussions and vignette-like statements to explore participants’ attitudes toward elder abuse. These were followed by open-ended questions. The transcripts from the focus groups were analyzed thematically and resulted in four main themes: (a) varied associations of the term “abuse,” (b) judging elder abuse situations in terms of abuse and severity, (c) self-identification with elder abuse, and (d) prevention of elder abuse. Study findings demonstrated that older persons hold views that are partly different from the views of professionals. Furthermore, perceptions of older persons could be stratified based on the socioeconomic status of the participants. These diverging perspectives reflect the heterogeneity of the senior citizen population and highlight the need for research cognizant of these differences. The results of this study provide strategies for improved targeting of preventive measures, underline the importance of integrating the perspectives of older persons, and reveal the need to expand the commonly accepted definitions of elder abuse so that they better reflect the affected individuals.